Characteristics Of Tabah Bamboo Activated Carbon Produced By Physical And Chemical Activations - Putra Negara, Dewa Ketut (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
In activated carbons (AC’s) production, activation process has a significant role toward characteristics of AC’s yielded.  The aim of this research is to investigate the activated carbons (AC’s) characteristics of tabah bamboo (Gigantochloc nigrociliata) manufactured by physical and chemical activations. Physical activation was carried out by heating up to 800° C, holding at that temperature during 1.5 hours under N 2 flow. Chemical activation was undertaken by mixing a carbon precursor with activating agent (H 3 PO 4 ) with weight ratio 1:1 during 6 hours. The mixed carbon precursor and H 3 PO 4 was then heated up to 700° C, soaked during 1.5 hours under N 2 flow. The results show that activated carbon (AC) provided by chemical activation has higher fix carbon and carbon (C) contents and lower ash, moisture and volatile then physical activation. AC manufactured by chemical activation yields 85.47 % fix carbon and 86.33 % carbon, meanwhile AC produced by physical activation has 82.28 % fixed carbon and 84.16.% carbon. Both types of activation give proximate analysis value that have fulfilled of Indonesian National Standard of AC (SNI 06-3730-1995)